Answer:
[tex]f(x) = 4\times (3)^{x}[/tex].
Step-by-step explanation:
Exponential functions are in the form [tex]f(x) = a\, \left(b^{x}\right)[/tex], where [tex]a[/tex] and [tex]b[/tex] are constants with [tex]b > 0[/tex].
In this question, the function should satisfy that [tex]f(2) = 36[/tex] and [tex]f(3) = 108[/tex]. Hence, constants [tex]a[/tex] and [tex]b[/tex] should ensure that:
[tex]a \cdot b^2 = f(2) = 36[/tex], and
[tex]a \cdot b^3 = 108[/tex].
Rewrite the left-hand side of the second equation: [tex]a \cdot b^{3} = a \cdot b^2 \cdot b[/tex].
Substitute the first equation [tex]a \cdot b^{2} = 36[/tex] into the second:
[tex]a \cdot b^2 \cdot b = 108[/tex].
[tex]36\, b = 108[/tex].
[tex]\displaystyle b = \frac{108}{36} = 3[/tex].
Substitute [tex]b = 3[/tex] into either equation (for example, the first equation) and solve for [tex]a[/tex]:
[tex]a \cdot 3^2 = 36[/tex].
[tex]a = 4[/tex].
Hence, the exponential function [tex]f(x) = a\cdot b^{x} = 4 \times (3)^{x}[/tex] should satisfy the requirements of this question.